Reproducing opportunistic connectivity traces using connectivity models - Thabotharan, Kathiravelu; Pears, A. (ACM New York, NY, USA ©2007, 2007)
Opportunistic networking is a new communication paradigm which explores the potential of inter-device contacts due to human mobility [3, 5]. Intermittent connectivity, non existence of an end-to-end path between nodes and extreme dynamism in topological structure are inherent characteristics of opportunistic networking [2, 5]. In opportunistic networking devices make control and management decisions by themselves with locally available information. The unique differences that draw the line between opportunistic networking and other legacy networking environments call for newer approaches for systems development.